G170(P) Use of brief multiprofessional simulation to improve confidence and skills in managing child and adolescent mental health crises out of hours. (12th March 2018) - Bandara, M; Lumley, E; Fernando, M; Bahry, R; Bhat, M; Anpananthar, A; Chester, L; Barry, T
Abstract : Background: The benefits of using simulation to improve skills and competence in clinical education is well established. A learning need was identified in managing out-of-hours CAMHS (Children and Adolescent Mental Health Service) emergencies, for junior medical trainees. It was recognised that learning could be augmented by widening participation across disciplines and professions. A pilot simulation delivered six months earlier to junior doctors on psychiatric rotation was well received and showed improved confidence. Methods: The session, comprised an introductory talk and two simulated scenarios, designed to address issues such as capacity, safeguarding, confidentiality and agitation. The training was delivered by a Consultant Paediatrician, Consultant Psychiatrist, a Fellow in Medical Education, Paediatric Registrar and two external actors. A pre-session focus group with psychiatry and paediatric teams identified concerns with assessing paediatric mental health patients after hours and the logistics of referral pathways and resources. Simulation scenarios were formulated to address these concerns and mapped to the Royal College of Psychiatry and Royal College of Paediatrics and Child Health training curriculum. Pre and post session questionnaires were also completed. Results: Seven participants attended the first session that was delivered; five psychiatry trainees and two paediatric trainees. 15 participants attended the second session; nine psychiatry trainees, four paediatric nurses, one foundation trainee and one GP trainee. Individuals participated in each section of the two scenarios, increasing candidates' direct experience of the simulation. 100% of participants reported feeling confident in all the outcomes assessed, which was an improvement in all domains. 73% of all participants stated they would recommend the course to a colleague, and that it met their learning needs. Free text qualitative feedback indicated a wider range of paediatric mental health topics to be covered. Conclusions: In future sessions more equal representation amongst the multidisciplinary and inter-professional teams will be sought. The evidence from these sessions and the previous pilot demonstrates that this is an effective, and stimulating way to improve skills in this area. Participants also benefit from sharing knowledge across disciplines and professions whilst developing collaborative working relationships.